EKSISTENSI KATA SERAPAN DALAM AL-QUR’AN - Zuhriah, Zuhriah (JURNAL ILMU BUDAYA, 2016)
This paper focuses on a loan word (al-mu'arrab), the absorption method of vocabulary, itscharacteristics and its existence in the Qur'an which is always a debate among scholars. Ingeneral, the absorption of the vocabulary of a foreign language into Arabic is caused by themixing between Arabs to neighbouring countries due to trade relations, migration, war andexpansion of the Islam. The absorption process is done by changing the font, changing theline, adding another letter in the word, reducing the letters and others. As a result of thesechanges, people often do not realize that actually it is not native Arabic but the absorption ofother languages. Therefore, this paper also presents the characteristics of a loan word in orderto facilitate people in identification. Their absorption method and characteristics arepossessed by the vocabulary uptake Arabic signifies that its existence is recognized by thepublic, but its existence in the Qur'an is still a debate among scholars from the first until now.There are at least three scholars‟opinions in this regard. Most of them have stated that none ofthe Arabic loan word in the Qur'an and have also stated that in fact there are words that arenot native Arabic but the absorption of other languages. Last categories are the ones who tryto reconcile the two previous groups.Keywords: existence, absorption, al-mu'arrab